Peningkatan Hasil Belajar Tematik Terpadu Menggunakan Model CIRC Berbantuan Media Gambar di Kelas IV SDN 29 Kabupaten Pesisir Selatan: Improving Integrated Thematic Learning Outcomes Using the CIRC Model Assisted by Picture Media in Grade IV SDN 29 Pesisir Selatan District - Wiwil Arnita; Hendrizal Hendrizal; Khairul Azmi (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
This research is motivated by integrated thematic learning in grade IV SDN 29 South Coastal District, this study aims to determine the improvement of the integrated thematic learning process for theme 9 using the CIRC model for class IV SDN 29 Pesisir Selatan Regency. This research is a classroom action research (PTK) which consists of four stages, namely planning, implementation, observation, and reflection. This research was carried out in two cycles consisting of three meetings. This study uses a qualitative and quantitative approach, the subject of this research is the fourth grade educators and students at SDN 29 Pesisir Selatan Regency with a total of twelve students. The results showed an increase in student learning outcomes in class IV, this increase can be seen from the learning implementation planning (RPP) cycle I was 65% and cycle II 72.5%. implementation of learning on the aspect of educators in the first cycle is 67.15% and 75% in the second cycle. the implementation of learning on the aspects of students in the first cycle is 67.15% and the second cycle is 75%, the learning outcomes of students in the first cycle are 56% and the second cycle is 91.66%. thus it can be concluded that the CIRC model in class IV at elementary school in south coastal regency can improve student learning outcomes.while the results and conclusions in the form of simple present tense.